Temporal Trends in Physical Fitness and Obesity Among Brazilian Children and Adolescents Between 2008 and 2014 - Garcia-Hermoso, A (University of Alicante, 2020)
The research aims to assess the trend of the health-related physical fitness over a period comprising 2008-2014, in two cohorts of a voluntary Brazilian school aged children and adolescents. Data was obtained from the database of Project Sport Brazil. The sample comprised children and adolescents aged between 10-17 years, assessed in two cohorts: 2008-2009 (6,281) and 2013-2014 (4,052) from different Brazilian regions. Measurement of the health-related physical fitness included: sit-up abdominal test, sit and reach, nine-minute of running/walking test, and body mass index. Descriptive data analyses and Poisson Logistic Regression were used. Prevalence trends of unhealthy flexibility increased significantly for boys from 35.2% to 38.4% and girls 23.5% to 38.0%, while prevalence on unhealthy abdominal strength/resistance decreased significantly for boys from 35.9% to 30.0% and did not show differences over time for girls. Overweight/obesity increased significantly over time in boys from 18.9% to 23.7%, as well as in girls from 19.4% to 28.0%. Cardiorespiratory fitness (CRF) showed the highest variation over time with a significantly increase of the unhealthy zone for both, boys from 33.4% to 61.3% and girls 33.3% to 66.6%. Therefore, we emphasize the importance of implementation national campaigns and interventions promoting physical activity in order to improve health. © Faculty of Education. University of Alicante.
Keywords: Physical education; School children; Cardiometabolic health; Musculoskeletal health; Overweight